Crime Bites / Hawa Shafinaz Akaata Effandy - Akaata Effandy, Hawa Shafinaz (2021)
For ENT5530 Principles of Entrepreneurship Social Media Portfolio assignment, I decided to sell Crime Bites HQ products since I am one of their official registered agent. Crime Bites HQ is a food and beverages exporter located at G-65 Maxim Citylights, No. 25, Jalan Sentul Perdana, 51100 Kuala Lumpur. The company produced 4 chocolate-based products which are Chocolate Chunk Cookies with Callebaut Chocolate, Rocher Cookies with melted Hazelnut Chocolate, Naked Cookies: Chocolate Chunk Cookies and Buono! Brownies: Brownies Cookies with Almond Nibs. However, I decided to focus on selling only 2 of their products which are Naked Cookies and Buono! Brownies for the sake of this assignment.